2014
DOI: 10.1177/1535370214538745
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-dependent Mcl-1 cleavage and effect of Mcl-1 phosphorylation in ABT-737-induced apoptosis in human acute lymphoblastic leukemia cell lines

Abstract: ABT-737 is a BH3-mimetic that has a wide spectrum of single-agent activity against acute lymphoblastic leukemia (ALL) cell lines and xenografts. Previously, we reported that in response to ABT-737, ABT-737-resistant ALL cell lines showed an apparent increase in Mcl-1 (an anti-apoptotic Bcl-2 family protein that is not effectively inhibited by ABT-737) while ABT-737-sensitive ALL cell lines showed decreased Mcl-1 levels. Here we explored the mechanism of Mcl-1 cleavage by ABT-737 and the effect of adjacent phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
(126 reference statements)
3
5
0
Order By: Relevance
“…Bim) other than the proteins assessed in this study may affect ABT-737 in vitro responsiveness. In agreement with published data [ 57 , 58 ], we demonstrated that increasing concentrations of ABT-737 further decreased Bcl-xL and Mcl-1 expression only in MOLT-4, a sensitive cell line, inducing significant cell growth reduction and apoptosis at nanomolar concentration. By contrast, protein levels were not affected in CEM S cells, a resistant cell model, showing no significant changes of apoptosis induction even at micromolar doses.…”
Section: Discussionsupporting
confidence: 93%
“…Bim) other than the proteins assessed in this study may affect ABT-737 in vitro responsiveness. In agreement with published data [ 57 , 58 ], we demonstrated that increasing concentrations of ABT-737 further decreased Bcl-xL and Mcl-1 expression only in MOLT-4, a sensitive cell line, inducing significant cell growth reduction and apoptosis at nanomolar concentration. By contrast, protein levels were not affected in CEM S cells, a resistant cell model, showing no significant changes of apoptosis induction even at micromolar doses.…”
Section: Discussionsupporting
confidence: 93%
“…This is because MCL-1 is one of the substrates of caspase 3. (39)(40)(41) The observed increase in caspase activation and cleavage of key apoptotic substrates reinforces the notion that co-targeting BCL-xL and BCL-2 for degradation induces a robust pro-apoptotic response in SCLC cells, ultimately leading to reduced cell viability.…”
Section: Discussionsupporting
confidence: 73%
“…Another splicing factor, SRSF1, was not affected (data not shown). Because Mcl-1 can also be cleaved by caspases to generate a smaller protein fragment, ABT-737-treated cells were used as a positive control for caspase-mediated Mcl-1 cleavage (43). ABT-737 treatment resulted in the expected smaller fragment of approximately 22 kDa that was abrogated by co-treatment with caspase inhibitor Z-VAD-FMK.…”
Section: Saclac Alters the Ratio Of Pro-survival To Pro-apoptotic MCLmentioning
confidence: 99%